2007
DOI: 10.1002/mrc.2123
|View full text |Cite
|
Sign up to set email alerts
|

The structure, dynamics, and energetics of protein adsorption—lessons learned from adsorption of statherin to hydroxyapatite

Abstract: Proteins are found to be involved in interaction with solid surfaces in numerous natural events. Acidic proteins that adsorb to crystal faces of a biomineral to control the growth and morphology of hard tissue are only one example. Deducing the mechanisms of surface recognition exercised by proteins has implications to osteogenesis, pathological calcification and other proteins functions at their adsorbed state. Statherin is an enamel pellicle protein that inhibits hydroxyapatite nucleation and growth, lubrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 78 publications
3
67
0
Order By: Relevance
“…The heat of the ligand dilution in the buffer alone was subtracted from the titration data for each experiment. The data were analyzed to determine the binding stoichiometry (N), affinity constant (K a ), and other thermodynamic parameter of the reaction using origin software [30]. Titration of protein with GNP-Chl nanoconjugates was carried out at 25°C.…”
Section: Isothermal Titration Calorimetry (Itc)mentioning
confidence: 99%
“…The heat of the ligand dilution in the buffer alone was subtracted from the titration data for each experiment. The data were analyzed to determine the binding stoichiometry (N), affinity constant (K a ), and other thermodynamic parameter of the reaction using origin software [30]. Titration of protein with GNP-Chl nanoconjugates was carried out at 25°C.…”
Section: Isothermal Titration Calorimetry (Itc)mentioning
confidence: 99%
“…HAp nanoparticles, therefore, have been investigated as a carrier for delivery of drugs such as growth factors [219,220], antibiotics [5,[221][222][223][224][225] and anticancer drugs [5,226,227]. The adsorption/desorption characteristics [44,220,[228][229][230] and conformation changes [230][231][232][233][234][235] of various kinds of proteins (or peptides) on HAp surfaces have been studied. Mukhopadhyay et al [236] recently reported that HAp nanoparticle supplementation increases thermal stability of pectate lyase from Bacillus megaterium, that is, this enzyme can retain high activity at elevated temperatures (up to 90…”
Section: Carriers For Drug Protein and Gene Deliverymentioning
confidence: 99%
“…Recently, computational (in silico) studies have been gradually progressed to clarify the interaction between proteins (or peptides) and HAp surfaces [237][238][239]. Detailed information on the protein/peptide adsorptions can be found in the original papers or a recent review by Goobes et al [235].…”
Section: Carriers For Drug Protein and Gene Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…15,17 Some of the methods that can provide information on adsorbed protein orientation and tertiary (and quaternary) structure include fluorescence, [18][19][20][21] time-of-flight secondary-ion mass spectrometry, [22][23][24] nuclear magnetic resonance spectroscopy (NMR), 25,26 and amino acid labeling/mass spectrometry (AAL/MS). [27][28][29][30][31] Methods for the determination of secondary structure of adsorbed proteins include Fourier transform infrared spectroscopy, 32,33 surface enhanced Raman scattering, 34,35 and circular dichroism spectropolarimetry (CD).…”
Section: Introductionmentioning
confidence: 99%